2020
DOI: 10.1177/2047487320915338
|View full text |Cite
|
Sign up to set email alerts
|

Association between ideal cardiovascular health and risk of sudden cardiac death and all-cause mortality among middle-aged men in Finland

Abstract: Background Strong associations have been demonstrated between the American Heart Association’s cardiovascular health (CVH) metrics and various cardiovascular outcomes, but the association with sudden cardiac death (SCD) is uncertain. We examined the associations between these CVH metrics and the risks of SCD and all-cause mortality among men in Finland. Methods and results We used the prospective populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Sаmple sizes ranged from 616 to 1,012,418. Two studies [ 47 , 51 ] included only males. Participants, were adults 18 years and older with an age range from 18 to 107 years.…”
Section: Resultsmentioning
confidence: 99%
“…Sаmple sizes ranged from 616 to 1,012,418. Two studies [ 47 , 51 ] included only males. Participants, were adults 18 years and older with an age range from 18 to 107 years.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study conducted in Finland showed that baseline CVH status was strongly and linearly associated with the future risk of SCD and all-cause death. 10 In that study, ideal physical activity did not show an independent association with the risk of SCD, compared to poor physical activity, because the study included participants with high physical activity, which itself might be a cause of sudden death. 29 However, in our study, ideal physical activity, which included vigorous activity, was related to lower risks of both SCD and all-cause death.…”
Section: Discussionmentioning
confidence: 92%
“… 6 7 8 9 In a recent study conducted in Finland, a high CVH score at baseline substantially reduced the risk of SCD among middle-aged men. 10 Although several studies have assessed the incidence of SCD, 11 limited data are available regarding the predictors of SCD in older adults. 12 13 14 The effects of changes in CVH status, in particular, over time on SCD in older adults have not been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of SCD and all-cause mortality decreased continuously with increasing score of CVH metrics across the range 2-7. 8 This study emphasizes that ideal CVH metrics are strongly inversely associated with the risk of SCD and all-cause mortality. Early intervention for ideal CVH is anticipated to further reduce the residual risk of SCD.…”
mentioning
confidence: 76%